Bioregulators on seed germination and seedling growth of sweet basil - Castro, Larissa Santos; Nobre, Danúbia Aparecida Costa; Hurtado, Daniel Andrés Villegas; Macedo, Willian Rodrigues (Comunicata Scientiae, 2020)
Basil (Ocimum basilicum L.) plants have multiple uses, ranging from spice to cosmetic purpose, besides being a source of essential oil and aromatic. These plants were commonly propagated by seed, however, few agrotechnologies are used to enhance the seed germination and initial growth in this crop. For this reason, our research aimed to evaluate aspects of seed germination of Ocimum basilicum L. cv. Limoncino, subjected to different bioregulators applied via substrate imbibition. The experiment was carried out in completely randomized design, with four treatments, as follows: T1: control (distilled water), T2: T13 a solution of a product formulated based on indolbutyric acid + naphthalene acetic acid + gibberellic acid (0.2 mL L-1, Liko Química), T3: gibberellic acid (0.5 mM L-1, progibb-400®) and T4: brassinosteroids (0.1 mM L-1). We evaluated: germination rate, germination speed index (GSI), first count, root and shoot length and chlorophyll a, b, total and carotenoids. The bioregulators did not influence germination, first count, GSI and photosynthetic leaf pigment, but application of gibberellic acid and brassinosteroids improve the shoot and root length, respectively. The gibberellic acid and brassinosteroids are promising bioregulators for stimulating initial basil growth.